Análise de riscos ambientais da exploração e produção do gás natural no Rio Grande do Norte - Rocha, Carlos Eduardo Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
Natural gas (NG) is a resource of great importance in the energy matrix of the state of Rio Grande do Norte (RN) that serves different sectors, and has the advantage of being less polluting when compared to fossil fuels. The exploration and production activities of the natural gas industry have had significant environmental impacts. The present study analyzed the process of exploration and production of natural gas in Rio Grande do Norte, to identify the environmental impact risks resulting from these activities. The analysis used reports from the National Petroleum, Natural Gas and Biofuel Agency (ANP) to characterize the scenario of natural gas production in the RN, then based on the literature, it was identified the environmental aspects and the possible risks of environmental impacts and for In order to estimate the environmental vulnerability of the exploration and production activities through a non-qualitative analysis, a probability-of-occurrence matrix was developed that showed that the exploration activities present higher levels of environmental richness, and the physical means alone and atmosphere and the biotic environment are more vulnerable to the impacts of the natural gas industry in general.
Keywords: Bacia potiguar; Meio ambiente; Combustível fóssil; Probabilidade de ocorrência; Consequência; Potiguar basin; Enviroment; Fossil fuel; Probability of occurence; Consequence; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA